Educational Interventions to Improve Pharmacy Students’ Empathy Towards Geriatrics: A Systematic Review - Hening Pratiwi; Susi Ari Kristina; Anna Wahyuni Widayanti; Yayi Suryo Prabandari (Indonesian Journal of Pharmacy, 2022)
Empathy is defined as the ability to understand other's feelings, thereby allowing them to feel understood. Empathy must be cultivated in the educational method to help pharmacy students to learn about patients, particularly the elderly. The main objective of this systematic review was to find, evaluate, and synthesize studies about educational interventions that improve the empathy of pharmacy students towards geriatrics. Three databases (PubMed, Science Direct, and Google Scholar) searched for articles with criteria that were educational intervention articles and focused on outcome measures related to improving empathy (or its subdivision) towards geriatrics. The Medical Education Research Study Quality Instrument was used to assess the possibility of bias. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to guide this review. Of the nine included studies, eight studies have been designed with quasi-experimental pre-post-test measurements. Four studies were carried out at the university in the United States, two in Malaysia, one in Australia, one in Brazil, and one in Singapore. Three studies used simulation and three studies used direct interaction with the elderly, as an educational intervention. Significant increase in empathy reported that 8 reviewed studies resulted from the statistically significant increase in empathy toward geriatrics. It was obvious that the educational intervention could help pharmacy students to develop empathy for the elderly. We recognize that the included studies are heterogeneous, implying that more research is needed to determine the best effective empathy education methods. Transfer to practice and longer-term changes in empathy should also be considered as study outcomes in future investigations.